A Study on the Expected Risk Tolerance Mechanism of Child-Friendly Environment Transformation in High-Density Communities - Yan Liu; Xujie Wang; Yinan Sun (Land)
As urbanization intensifies, high-density communities have become a dominant urban form, making Child-Friendly Community (CFC) development crucial for sustainable urban growth. However, transforming these communities poses challenges, particularly regarding residents’ risk perceptions—an area largely overlooked in existing research. To address this gap, this study introduces “Risk Tolerance (RT)” as a key variable and constructs a multidimensional model of Child-Friendly Community Transformation Risk Tolerance (CFCTRT) to examine its structure and influencing factors. Based on survey data from residents in high-density communities in China’s first- and second-tier cities, Structural Equation Modeling (SEM) is used for empirical analysis. The results show that residents exhibit lower tolerance toward changes in safety, economy, and daily life, but higher tolerance in resource and aesthetic dimensions. Expectations for CFCs and satisfaction with current communities both positively influence CFCTRT, with satisfaction also mediating the relationship between expectations and tolerance. These findings provide a novel perspective on residents’ psychological responses to CFC transformations and offer empirical support for more inclusive and adaptive urban planning strategies.